The Role of Autophagy in the Mother-to-Child Transmission of Pregnant Women With a High Level of HBV DNA - Gao, Hong; Xu, Ling; Fan, Zihao; Zhang, Xiangying; Duan, Zhongping; Ren, Feng (Frontiers in Cellular and Infection Microbiology, 2022)
Background Mother-to-child transmission (MTCT) is the most common propagation mode of hepatitis B virus (HBV) transmission. Exploring the mechanisms of HBV MTCT is the key to protect infant from infection. In this study, we aim to clarify the important role of autophagy in the prevention of HBV MTCT. Methods A total of 169 placental samples were collected in this study, includes 144 HBV positive pregnant women and 25 normal pregnant women. In vitro, JEG-3 cells were treated with serum contained different HBV viral loads. Electron microscope was used to observed the number of autophagosome. RT-qPCR and western blotting were used to measure the expression level of autophagy relative genes and proteins respectively. Immunofluorescence was used to analyzed the expression of LC-3 of the frozen section of placental tissue. Results According to the number of autophagosomes and the expression level of autophagic genes mRNA and protein, autophagy was increased in HBV maternal placenta. Among the control, low viral load, medium viral load and high viral load groups, autophagy was significantly up-regulated with the increase of HBV viral loads. Also, autophagy was increased in the HBeAg positive pregnant women compared with their HBeAg negative counterparts. Also, autophagy in infant-infected group was up-regulated compared with infant-uninfected group. In vitro, choriocarcinoma JEG-3 cells were treated with the different HBV viral loads or different time incubation, the mRNA and protein of autophagy related genes was maximum expression in the medium viral load or treatment in a short period, but decreased in the high viral load treatment or with long-term HBV exposure. Conclusion Our study determines the high levels of viremia could be the cause of both increase autophagy activities and MTCT. Autophagy was significantly up-regulated in pregnant women with high viral load or HBeAg positive, which plays an important part in the HBV MTCT.